Factors Affecting Employee Performance (Literature Study of Human Resource Management) - Andri (Takaza Innovatix Labs Ltd., 2026)
This study aims to investigate the factors that influence employee performance through a literature review in the field of Human Resource Management. The factors studied include motivation, job satisfaction, competence, organizational culture, leadership, and work support. Employee performance is considered a key factor in achieving organizational success in today's competitive market. Human Resource Management (HRM) plays a central role in managing factors that influence employee performance, such as recruiting, developing, motivating, and retaining qualified employees. This study uses a literature analysis method (library research) that collects data from various relevant literature sources. By analyzing and synthesizing these findings, they can identify the factors that most influence employee performance. This data will be analyzed qualitatively to identify factors that influence employee performance. The factors to be studied include the work environment, job satisfaction, and work motivation. These factors can interact and influence each other in influencing employee performance. The results of this library research are: 1) the work environment influences employee performance; 2) job satisfaction influences employee performance; 3) and work motivation influences employee performance